Dynamic factors of inflation in Pakistan - Waqar Ali Ather Bukhari; Hooi Hooi Lean; Seemab Rana; Wong Hock Tsen (Malaysian Finance Association, 2025)
This paper examines the long run and short run associations between inflation rate and its regressors such as unemployment rate, money supply growth rate, interest rate, labor productivity growth rate, output gap and inflationary shocks in Pakistan. The research specifically addresses how these macroeconomic variables influence inflation dynamically and whether inflationary shocks have asymmetric effects. Motivation: The persistent inflation in Pakistan, driven by both monetary and real sector factors, emphasizes the necessity for a comprehensive empirical investigation to support the formulation of effective economic policies. Data: The study uses annual data from 1991 to 2020, including inflation, unemployment, money supply, interest rate, labor productivity, and output gap. The data were collected from both monetary and real sectors including Federal Bureau of Statistics, State Bank of Pakistan (SBP), International Labor Organization Statistics (ILO) and World Development Indicators (WDI). Method/Tools: Bootstrap Non-linear Autoregressive Distributed Lag (NARDL) cointegration tests (McNown et al. 2018) is opted to identify the long run cointegration among exogenous and endogenous variables. This approach also captures asymmetric effects by analyzing how positives and negatives shocks influence inflation in Pakistan. Findings: The results show that there is a significant impact of labor productivity, output gap and unemployment rate on inflation rate. Monetary variables are also observed as the important drivers of inflation fluctuations. The findings suggest a contractionary monetary policy in the long run and expansionary monetary policy in the short run to stabilize inflation rate in Pakistan. This study also provides evidence on the positive impact of inflationary shocks on increase in inflation. Negative inflation shocks are found more influential than positive inflation shocks. Contributions: This study contributes to the inflation literature by introducing asymmetric dynamics using the NARDL approach and integrating real sector variables like labor productivity and output gap in Pakistan, offering new insights for monetary policy formulation.